PANDEMIK DI POLLS: CARA MEMPERSIAPKAN PEMILU POST COVID-19 (MENUJU PEMILU LOKAL INDONESIA TAHUN 2020) - Ratna Rosanti (Universitas Jenderal Ahmad Yani, 2020)
ABSTRACT This paper will specifically provide a preliminary assessment of the many risks that a COVID-19 pandemic can cause during elections and it is not impossible if what happens next is that holding an election will be far from honest and transparent. The emergence of a new era during the pandemic called New Normal where everyone must behave new in everyday life by prioritizing aspects of health will certainly have a significant influence in the implementation of elections. This paper begins by explaining why elections are an important part of democracy, and then looks at how the government's response to the pandemic and elections that will be held in the New Normal era will present significant solutions about the future of democracy itself. In this paper, the author also recommends several things related to the holding of elections during the pandemic. The main findings of this paper are: First, the presence of the virus itself can directly prevent voters from casting their votes at the polling stations and even affect the overall level of voter participation. Second, there are consequences of formally delaying the holding of elections which vary by type of regime (national or local). Third, some elements in the electoral cycle can be affected by the pandemic.